2008
DOI: 10.1080/08276331.2008.10593431
|View full text |Cite
|
Sign up to set email alerts
|

Business Plans: Are They Relevant to Venture Capitalists?

Abstract: Relevance of the traditional business plan in the investment decisions made by venture capitalists for entrepreneurs has recently been a subject of debate. Some people view business plans to be a main input in the decision making process of investors. Others see business plans as having limited prominence, having been replaced by other means of inspiring confidence in potential investors. This study is designed to empirically investigate the relevance of a business plan in today's fast-paced and dynamic enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…Research in entrepreneurship is immersed in an intense debate on the value of business planning. Most previous empirical findings move along the same lines and come to similar conclusions: the process of creating a business plan is essential for successfully completing a project (Barringer and Gresock, 2008;Honig, 2004) and enables students to enhance their reflection and planning skills (Ashamalla et al, 2008). It even increases the chances of success in launching a business, helps guide risk-taking and supports the performance of certain activities during the initial start-up phase (Brinckmann et al, 2010;Giunipero et al, 2008), and also has a positive influence on students' entrepreneurial competences (Tounés et al, 2014).…”
Section: Business Plansmentioning
confidence: 63%
See 1 more Smart Citation
“…Research in entrepreneurship is immersed in an intense debate on the value of business planning. Most previous empirical findings move along the same lines and come to similar conclusions: the process of creating a business plan is essential for successfully completing a project (Barringer and Gresock, 2008;Honig, 2004) and enables students to enhance their reflection and planning skills (Ashamalla et al, 2008). It even increases the chances of success in launching a business, helps guide risk-taking and supports the performance of certain activities during the initial start-up phase (Brinckmann et al, 2010;Giunipero et al, 2008), and also has a positive influence on students' entrepreneurial competences (Tounés et al, 2014).…”
Section: Business Plansmentioning
confidence: 63%
“…Furthermore, the results of Brinckmann et al (2010) are partly confirmed, according to which teaching entrepreneurship reduces uncertainty in decision-making, since in our case the decision-making competence is ninth in terms of level of perception and second in attainment. The results of Ashamalla et al (2008) are also confirmed, since they CA1 CA2 CA3 CA4 CA5 CA6 CA7 CA8 CA9 CA10 CA11 CA12 CA13 CA14 CA15 CA16 CA17 Fictitious 7.86 7.86 7.86 7.86 7.86 7.86 6.06 6.06 7.61 7.04 7.04 4.87 6.91 7.23 4.87 6.54 6.26 Real 8.05 8.05 8.05 8.05 8.05 8.05 6.41 6.41 7.76 7.21 7.21 5.02 6.88 7.19 5.02 6.91 6.37 CA18 CA19 CA20 CA21 CA22 CA23 CA24 CA25 CA26 CA27 CA28 CA29 CA30 CA31 CA32 CA33 CA34 Fictitious 6.82 6.82 6.26 6. 06 7.50 8.88 8.88 7.66 7.61 7.53 7.59 6.54 7.62 7.17 4.87 7.46 7.30 Real 6.84 6.84 6.37 6.41 7.26 8.67 8.67 7.86 7.76 7.76 7.42 6.91 7.27 7.22 5.02 7.42 7.32 showed that creating a business plan offers a learning context in which students can boost their planning skills and, in our case, project management competence is sixth in terms of level of perception and eighth in attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Cook, Belliveau, & Sandberg (2004) consideran que el desarrollo de un BP de calidad es un ingrediente esencial para el éxito emprendedor. Longenecker et al (2010) sostienen que, son un requisito previo que ayuda al emprendedor a comunicar su visión y enfocarse en los aspectos y las actividades más importantes, y juegan un papel crucial en la evaluación global de una nueva empresa por parte de inversionistas, aumentando las posibilidades de éxito (Ashamalla, Orife, & Abel, 2008). Por lo tanto, los estudiantes que han aprendido a desarrollar BPs deben mostrar un mayor conocimiento y habilidades emprendedoras, autoeficacia e intención de iniciar una nueva empresa (Lange, Marram, Jawahar, Yong, & Bygrave, 2011;Honig, 2004).…”
Section: Desarrollo De Planes De Negocio En La Educacion Emprendedoraunclassified
“…Many authors and researchers advocate for writing little or no business plan at all (Brinckmann, Grichnik, & Kapsa, 2010;Gerber, 2010;Gumpert, 2002;Guttman, 2015). Further research shows that the venture capital community is open to investing in firms with no startup plans (Ashamalla, Orife, & Abel, 2008). Castrogiovanni (1996) argues that many great successes started without business plans.…”
Section: Antecedents and Characteristics Of The New Venture Creation mentioning
confidence: 99%